Benzo[c]carbazole derivatives produced by an effective Diels–Alder reaction: synthesis and structure–activity-relationship for surface coating. Issue 79 (9th August 2016) - Feng, Xue-Qing; Zhang, Fei; He, Xiao-Peng; Chen, Guo-Rong; Wu, Xin-Yan; Sha, Feng
Abstract : We demonstrate the use of an effective Diels–Alder reaction to produce a library of heterocyclic, polyaromatic benzo[ c ]carbazole derivatives with good corrosion inhibitive potency for copper against HCl. Abstract : We show the construction of a library of heteroatom-fused benzo[ c ]carbazole derivatives by a Diels–Alder reaction as effective surface-coating materials against copper corrosion in an acidic medium.